(untitled) (International Seven Journal of Multidisciplinary, 2024)
The aim of the research was to study the role of counselor in school today, and specifically: to present the educational practice of career guidance, as well as point out the prospects and challenges faced by the supervisor in the daily school. Thus, the problem that gave rise to the featured article was: The counselor is leading actor or supporting role in the school? Thus an analysis must consist of the theoretical Chalita (2005), Grinspum (2003), Luck (2001), Pimentel (2006) Urbanetz (2008), among others, to underpin and support this work. Armed with this benchmark, we set up the development work, through an exploratory approach - qualitative. Reaching the conclusion, based on the context presented one of the challenges currently presented to this work is to find support outside the school, to carry out the rescue work of the student’s world of drugs, violence, social and family which influences the school environment. It is an arduous task but not impossible for this professional education.